Design and the environment (Video Education Australasia, 2010)
On this DVD training - with over 2 hours of videos - David Revoy explains step-by-step his 3D paint-over techniques. The training starts with an instroduction to Blender 2.5, to provide 2D artists with not much 3D experience a quick overview of the key features of Blender. It introduces the basics of the UI, modeling meshes and setting up light and rendering. This render is then taken to MyPaint and GIMP for further processing, importing and setting up several layers and showing how to efficiently add detail, texture and more dramatic lightning with manual paint-overs and layering techniques.